Fiber sizing agent and use thereof
The fiber sizing agent, composed of a specific epoxy compound and a surfactant, addresses the issue of fuzz-induced property reduction in fiber-reinforced composites by enhancing adhesion and suppressing fuzz, thereby improving the physical properties of the composite materials.
Patent Information
- Application Number
- JP2023178657
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-30
AI Technical Summary
Existing fiber sizing agents improve adhesion to epoxy resins or radical polymerization matrix resins but reduce various physical properties due to fuzz formation.
A fiber sizing agent containing a specific epoxy compound with a structural unit represented by a general formula and a surfactant, which provides adhesion to the matrix resin and suppresses fuzz formation.
The fiber sizing agent achieves excellent adhesion to the matrix resin while preventing fuzz, resulting in fiber-reinforced composite materials with improved physical properties.
Smart Images

Figure 2025068703000001 
Figure 2025068703000002 
Figure 2025068703000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a fiber sizing agent and its uses. In particular, the present invention relates to a fiber sizing agent, a fiber strand using the same, and a fiber-reinforced composite material. [Background technology]
[0002] Fiber-reinforced composite materials in which plastic materials (called matrix resins) are reinforced with various synthetic fibers are widely used in automobiles, aerospace, sports and leisure, general industrial applications, etc. Fibers used in these composite materials include various inorganic fibers such as carbon fibers, glass fibers, and ceramic fibers, and various organic fibers such as aramid fibers, polyamide fibers, and polyethylene fibers. These various fibers are usually manufactured in the form of filaments, and then processed into sheet-shaped intermediate materials called unidirectional prepregs by the hot melt method or drum winding method, processed by the filament winding method, and sometimes processed into woven fabrics or chopped fiber shapes, and then used through various advanced processing steps.
[0003] Epoxy resins are widely used as matrix resins in fiber-reinforced composite materials. In addition to epoxy resins, unsaturated polyester resins, vinyl ester resins, acrylic resins, etc. are also used as radical polymerization matrix resins. In order to improve the mechanical strength of fiber-reinforced composite materials, the wettability and adhesiveness of the matrix resin to the fibers are important, and sizing agents that improve the wettability and adhesiveness of the fibers to the above-mentioned epoxy resins and radical polymerization matrix resins have been proposed (for example, Patent Documents 1 and 2, etc.). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-169260 A [Patent Document 2] JP 2005-179826 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, although the sizing agents described in Patent Documents 1 and 2 improve the adhesion of reinforcing fibers to epoxy resins and radical polymerization matrix resins, various physical properties are degraded due to fuzz.
[0006] An object of the present invention is to provide a fiber sizing agent which can provide a fiber strand of excellent quality by achieving both good adhesion to a matrix resin and suppression of fuzz, and to provide a fiber strand and a fiber-reinforced composite material which use the same. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above-mentioned problems, the present inventors discovered that a fiber sizing agent containing a specific epoxy compound (A) and a surfactant (B) can solve the above-mentioned problems, and arrived at the present invention.
[0008] That is, the present invention includes the following embodiments. <1> A fiber sizing agent comprising an epoxy compound (A) having a structural unit represented by the following general formula (1) and a surfactant (B). [ka] (In formula 1, * represents the bonding position to a primary carbon atom or a secondary carbon atom.) <2> The epoxy equivalent of the non-volatile content of the fiber sizing agent is 100 to 10,000 g / eq. <1> The fiber sizing agent according to claim 1. <3> the fiber sizing agent optionally contains an epoxy compound (C) other than the epoxy compound (A), and a weight ratio ((A+C) / B) of the total of the epoxy compound (A) and the other epoxy compound (C) to the surfactant (B) in the non-volatile content of the fiber sizing agent is 0.1 to 10; <1> or <2> The fiber sizing agent according to claim 1. <4> The complex viscosity of the non-volatile content of the fiber sizing agent at 25°C, strain 0.005, and frequency 1 Hz is 1 x 10 2 ~1×10 5 Pa·s, <1> ~ <3> 2. The fiber sizing agent according to claim 1 . <5> The ester value of the non-volatile content of the fiber sizing agent is 1.5 to 500 mgKOH / g. <1> ~ <4> 2. The fiber sizing agent according to claim 1 . <6> <1> ~ <5> A fiber strand having the fiber sizing agent according to any one of claims 1 to 5 adhered thereto. <7> A matrix resin; <6> and the fiber strand according to claim 1. <8> The matrix resin is a thermosetting resin. <7> The fiber-reinforced composite material according to claim 1. Effect of the Invention
[0009] The fiber sizing agent of the present invention can achieve both adhesion to a matrix resin and suppression of fluff. By using the fiber strand of the present invention, a fiber-reinforced composite material having excellent physical properties can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Each component of the fiber sizing agent of the present invention will now be described in detail. [Epoxy compound (A)] The fiber sizing agent of the present invention contains an epoxy compound (A) having a structural unit represented by general formula (1). [ka] (In formula 1, * represents the bonding position to a primary carbon atom or a secondary carbon atom.)
[0011] In formula 1, each * may be a bonding position to a primary carbon atom or a secondary carbon atom, however, from the viewpoint of fuzz suppression, it is preferable that at least one * is a bonding position to a secondary carbon atom, and it is more preferable that each * is a bonding position to a secondary carbon atom. From the viewpoint of adhesion to the matrix resin, the epoxy compound (A) preferably contains a compound having 1 to 9 structural units represented by general formula (1) in the molecule. The upper limit of the number of the structural units in the molecule is more preferably 8, further preferably 7, and further preferably 6. On the other hand, the lower limit of the number of the structural units in the molecule is more preferably 2, and further preferably 3. Also, for example, 2 to 9 is more preferable, and 2 to 8 is further preferable.
[0012] The epoxy compound (A) is not particularly limited as long as it has a structural unit represented by general formula (1). Examples of the epoxy compound (A) include epoxidized fatty acid esters, epoxidized fatty acids, epoxidized alcohols, epoxidized fatty acid amides, and epoxidized olefins.
[0013] The epoxidized fatty acid ester includes a compound having a structure in which a fatty acid in which the double bond in the molecule is epoxidized and an alcohol are esterified. The fatty acid having an epoxidized double bond in the molecule is not particularly limited, but from the viewpoint of suppressing fuzz, an epoxidized fatty acid having 8 to 36 carbon atoms is preferred, and it may be an epoxidized monovalent fatty acid or an epoxidized polyvalent fatty acid. Examples of fatty acids having an epoxidized double bond in the molecule include epoxidized myristoleic acid, epoxidized palmitoleic acid, epoxidized sapienic acid, epoxidized oleic acid, epoxidized elaidic acid, epoxidized vaccenic acid, epoxidized gadoleic acid, epoxidized eicosenoic acid, epoxidized erucic acid, epoxidized nervonic acid, epoxidized linoleic acid, epoxidized eicosadienoic acid, epoxidized docosadienoic acid, epoxidized linolenic acid, epoxidized pinolenic acid, epoxidized eleostearic acid, epoxidized mead acid, epoxidized dihomo-γ-linolenic acid, epoxidized eicosatrienoic acid, epoxidized stearidonic acid, epoxidized arachidonic acid, epoxidized eicosatetraenoic acid, epoxidized adrenic acid, epoxidized bosseopentaenoic acid, epoxidized eicosapentaenoic acid, epoxidized osbondoic acid, epoxidized sardine acid, epoxidized tetracosapentaenoic acid, epoxidized docosahexaenoic acid, and epoxidized herring acid. Moreover, the epoxidized polyvalent fatty acid may, for example, be epoxidized dimer acid.
[0014] The alcohol to be esterified with the epoxidized fatty acid in the molecule is not particularly limited, but includes monohydric alcohols and polyhydric alcohols, and from the viewpoint of suppressing fluff, alcohols having 1 to 24 carbon atoms are preferred. Examples of monohydric alcohols include methyl alcohol, ethyl alcohol, propyl alcohol, butyl alcohol, pentanol, hexanol, heptanol, nonanol, octanol, decanol, undecanol, dodecanol, tridecanol, tetradecanol, pentadecanol, hexadecanol, heptadecanol, octadecanol, nonadecanol, icosanol, henicosanol, docosanol, tricosanol, and tetracosanol. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, butylene glycol, trimethylolpropane, glycerin, erythritol, pentaerythritol, sorbitol, and sorbitan.
[0015] Examples of epoxidized fatty acid esters include esters of epoxidized monovalent fatty acids and monohydric alcohols, and esters of epoxidized monovalent fatty acids and polyhydric alcohols. From the viewpoint of achieving both fuzz suppression and adhesion to the matrix resin, the esters of epoxidized monovalent fatty acids and polyhydric alcohols are preferred.
[0016] As the ester of an epoxidized monovalent fatty acid and a monovalent alcohol, from the viewpoint of achieving both fuzz suppression and compatibility with the matrix resin, epoxidized octyl linoleate, epoxidized butyl linoleate, epoxidized methyl linoleate, epoxidized octyl oleate, epoxidized butyl oleate, epoxidized methyl oleate, epoxidized octyl linolenate, epoxidized butyl linolenate, and epoxidized methyl linolenate are preferred.
[0017] As the ester of epoxidized monovalent fatty acid and polyhydric alcohol, from the viewpoint of achieving both fuzz suppression and adhesion to the matrix resin, preferred are monoglycerides, diglycerides and triglycerides consisting of ester compounds of glycerin with epoxidized linseed oil, epoxidized soybean oil, epoxidized corn oil, epoxidized cottonseed oil, epoxidized perilla oil, epoxidized safflower oil, epoxidized tung oil, epoxidized sunflower oil, epoxidized sesame oil, epoxidized oleic acid, epoxidized linoleic acid, epoxidized linolenic acid, epoxidized eicosapentaenoic acid, epoxidized docosahexaenoic acid, epoxidized arachidonic acid or the like, whose intramolecular double bonds have been epoxidized.
[0018] The epoxidized fatty acid may be a compound having a structure in which a fatty acid having a double bond in the molecule is epoxidized, and the fatty acids in which the double bond in the molecule is epoxidized, which are listed as the components of the epoxidized fatty acid ester described above, are preferred.
[0019] The epoxidized alcohol is not particularly limited as long as it is a compound having a structure in which an alcohol having a double bond in the molecule is epoxidized, but from the viewpoint of suppressing fuzz, alcohols having 8 to 36 carbon atoms are preferred.
[0020] The epoxidized fatty acid amide is not particularly limited as long as it is a compound having a structure in which an intramolecular double bond is amide with an epoxidized fatty acid and an organic amine. The organic amine whose intramolecular double bond is amide with an epoxidized fatty acid is not particularly limited as long as it is a primary amine and / or a secondary amine, but a primary amine is preferred in terms of adhesion to the matrix resin.
[0021] The epoxidized olefin is not particularly limited as long as it is a compound having a structure in which the double bond of an internal olefin is epoxidized, but from the viewpoint of suppressing fuzz, an internal olefin having 8 to 36 carbon atoms is preferred.
[0022] The epoxy compound (A) may be an aliphatic epoxy resin or an aromatic epoxy resin, and preferably contains an aliphatic epoxy resin in terms of suppressing fuzz. The epoxy compound (A) may be used alone or in combination of two or more kinds.
[0023] The number average molecular weight (Mn) of the epoxy compound (A) is not particularly limited, but from the viewpoint of suppressing fuzzing, it is preferably 100 to 2000. The upper limit of the number average molecular weight is more preferably 1800, further preferably 1600, and particularly preferably 1400. On the other hand, the lower limit of the number average molecular weight is more preferably 200, further preferably 250, and particularly preferably 300. The number average molecular weight (Mn) in the present invention refers to a value measured by gel permeation chromatography (GPC) under the following measurement conditions and converted into polyethylene glycol. (GPC measurement conditions) Apparatus: Apparatus name "HLC-8320GPC" (manufactured by Tosoh Technosystems Co., Ltd.) Columns: "KF-402HQ" and "KF-403HQ" (both manufactured by Resonac [SHODEX]) Mobile phase: Tetrahydrofuran (THF) Flow rate: 0.30ml / min Sample volume: 10 μl (sample concentration 2 mg / ml) Column temperature: 40℃
[0024] The epoxy equivalent of the epoxy compound (A) is preferably 100 to 500 g / eq in terms of adhesion to the matrix resin. The upper limit of the epoxy equivalent is more preferably 400 g / eq, further preferably 350 g / eq, and particularly preferably 300 g / eq. On the other hand, the lower limit of the epoxy equivalent is more preferably 120 g / eq, further preferably 140 g / eq, and particularly preferably 160 g / eq. Also, for example, 120 to 400 g / eq is more preferable, and 140 to 300 g / eq is more preferable. The epoxy equivalent is based on JIS-K-7236:2001 (corresponding to ISO 3001:1999).
[0025] The number of epoxy groups in the epoxy compound (A) is preferably 1 to 10 in terms of adhesion to the matrix resin. The upper limit of the number of epoxy groups is more preferably 9, further preferably 8, and particularly preferably 7. On the other hand, the lower limit of the number of epoxy groups is more preferably 1.5, further preferably 2, and particularly preferably 2.5. Also, for example, 1.5 to 9 is more preferable, and 2 to 8 is even more preferable. The number of epoxy groups is a value calculated from the epoxy equivalent and the number average molecular weight Mn according to the following formula. (Number of epoxy groups)=Mn / (epoxy equivalent)
[0026] It is preferable that the epoxy compound (A) has an ester group in terms of adhesion to the matrix resin and suppression of fluff. When the epoxy compound (A) has an ester group, the number of ester groups is preferably 1 to 10 in terms of adhesion to the matrix resin and suppression of fuzz. The upper limit of the number of ester groups is more preferably 8, further preferably 6, and particularly preferably 4. On the other hand, the lower limit of the number of ester groups is more preferably 1.5, further preferably 2, and particularly preferably 2.5. Also, for example, 1.5 to 8 is more preferable, and 2 to 7 is more preferable. The number of ester groups is a value calculated from the number average molecular weight Mn and the ester value according to the following formula. (Number of ester groups) = (Ester value) × Mn / 56100 The ester value is a value calculated in accordance with JIS K-0070:1992 5. Ester value.
[0027] When the epoxy compound (A) has an ester group, it is preferable that the number of epoxy groups relative to the number of ester groups in the epoxy compound (A) (number of epoxy groups / number of ester groups) is 0.1 to 5 in terms of suppressing fuzz. The upper limit of the number of epoxy groups relative to the number of ester groups is more preferably 4.5, further preferably 4, and particularly preferably 3.5. On the other hand, the lower limit of the number of epoxy groups relative to the number of ester groups is more preferably 0.5, further preferably 1.0, and particularly preferably 1.5. Also, for example, it is more preferably 0.5 to 4.5, and further preferably 1.0 to 4.0. The number of epoxy groups and the number of ester groups are calculated by the above-mentioned method.
[0028] The method for producing the epoxy compound (A) is not particularly limited, and a known method can be adopted. The above-mentioned epoxy compounds are generally commercially available, and the fiber sizing agent of the present invention can use these commercially available epoxy compounds.
[0029] [Surfactant (B)] The fiber sizing agent of the present invention contains a surfactant (B). The surfactant (B) is not particularly limited, but may be appropriately selected from known surfactants such as nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants. The surfactant (B) may be used alone or in combination of two or more. From the viewpoint of achieving the effects of the present application, the surfactant (B) preferably contains at least one selected from nonionic surfactants and anionic surfactants, and more preferably contains a nonionic surfactant.
[0030] The nonionic surfactant is not particularly limited as long as it is a nonionic organic compound having a hydrophilic group and a hydrophobic group. Examples of the hydrophilic group include a polyoxyethylene group, a polyoxyethylene / polyoxypropylene random copolymer group, a polyhydric alcohol group, and a hydroxyl group. Examples of the hydrophobic group include an alkyl group, an alkenyl group, an alkynyl group, an aryl group, an alkylaryl group, a polycyclic aryl group, and a polypropylene oxide group.
[0031] Examples of the alkyl group constituting the hydrophobic group include a methyl group, an ethyl group, a propyl group, a butyl group, a hexyl group, a 2-ethylhexyl group, a decyl group, a lauryl group, an isodecyl group, a tridecyl group, a cetyl group, a stearyl group, a behenyl group, and the like. The alkyl group may be primary, secondary, or tertiary, and may have a straight-chain or branched structure. Examples of alkenyl groups constituting the hydrophobic group include octenyl, nonenyl, decenyl, dodecenyl, tridecenyl, tetradecenyl, pentadecenyl, hexadecenyl, heptadecenyl, octadecenyl, eicosenyl, docosenyl, and tetracosenyl groups, which may have a branched or cyclic structure.
[0032] Examples of the alkynyl group constituting the hydrophobic group include an ethynyl group, a propynyl group, an isopropynyl group, a butynyl group, an isobutynyl group, a tert-butynyl group, a pentynyl group, a hexynyl group, an octynyl group, and a nonynyl group. Examples of the alkylaryl group constituting the hydrophobic group include a tolyl group, a xylyl group, a cumyl group, an octylphenyl group, a 2-ethylhexylphenyl group, a nonylphenyl group, a decylphenyl group, and a methylnaphthyl group, and there are no limitations on the position or number of the alkyl group.
[0033] Examples of polycyclic aryl groups constituting the hydrophobic group include a styrylphenyl group, a styrylmethylphenyl group, a styrylnonylphenyl group, an alkylstyrylphenyl group, a tristyrylphenyl group, a distyrylphenyl group, a distyrylmethylphenyl group, a tristyrylphenyl group, a benzylphenyl group, a dibenzylphenyl group, an alkyldiphenyl group, a diphenyl group, a cumylphenyl group, a naphthyl group, and a bisphenol group, and there are no limitations on the position or number of the substituent.
[0034] Examples of nonionic surfactants include alkylene oxide-added nonionic surfactants (higher alcohols, higher fatty acids, alkylphenols, styrenated phenols, benzylphenols, bisphenols, sorbitan, sorbitan esters, castor oil, hardened castor oil, etc., to which alkylene oxides such as ethylene oxide, propylene oxide, etc. (two or more of these can be used in combination) have been added), polyalkylene glycols to which higher fatty acids have been added, esters of polyhydric alcohols such as glycerin and sorbitan, fatty acids, and ethylene oxide / propylene oxide copolymers.
[0035] Examples of the higher fatty acids include capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, montanic acid, oleic acid, linoleic acid, linolenic acid, eleostearic acid, ricinoleic acid, erucic acid, coconut oil fatty acid, palm oil fatty acid, palm kernel oil fatty acid, beef tallow fatty acid, castor oil fatty acid, and rapeseed oil fatty acid.
[0036] From the viewpoint of suppressing fuzz, the nonionic surfactant preferably includes at least one selected from alkylene oxide-added nonionic surfactants (those having a structure in which an alkylene oxide such as ethylene oxide or propylene oxide (two or more of which can be used in combination) is added to a higher alcohol, a higher fatty acid, an alkylphenol, a styrenated phenol, a benzylphenol, a bisphenol, sorbitan, a sorbitan ester, castor oil, hydrogenated castor oil, or the like) and an ethylene oxide / propylene oxide copolymer, and more preferably includes at least one selected from those having a structure in which ethylene oxide is added to sorbitan, sorbitan ester, castor oil, or hydrogenated castor oil, and those having a structure in which ethylene oxide is added to polypropylene glycol (so-called Pluronic (registered trademark) type surfactants).
[0037] The number average molecular weight of the nonionic surfactant is preferably from 2,000 to 18,000, and more preferably from 3,000 to 6,000, from the viewpoint of sizing ability.
[0038] Examples of anionic surfactants include organic carboxylic acids (salts), sulfates (salts) of higher alcohols and higher alcohol ethers, organic sulfonic acids (salts), and phosphates (salts) of higher alcohols and higher alcohol ethers. From the viewpoint of emulsion stability, the anionic surfactant preferably contains at least one selected from sulfates (salts) of higher alcohols and higher alcohol ethers and phosphates (salts) of higher alcohols and higher alcohol ethers.
[0039] Specific examples of the anionic surfactant include alkyl sulfate salts, alkylaryl sulfate salts, polycyclic aryl sulfate salts, polyoxyalkylene alkyl ether sulfate salts, polyoxyalkylene alkylaryl ether sulfate salts (polyoxyalkylene nonyl phenyl ether sulfate salts, etc.), polyoxyalkylene polycyclic aryl sulfate salts (polyoxyalkylene tristyryl phenyl ether sulfate salts, polyoxyalkylene distyryl phenyl ether sulfate salts, polyoxyalkylene styryl phenyl ether sulfate salts, polyoxyalkylene styryl methyl phenyl ether sulfate salts, polyoxyalkylene distyryl methyl phenyl ether sulfate salts, polyoxyalkylene tristyryl methyl phenyl ether sulfate salts, polyoxyalkylene benzyl phenyl ether sulfate salts, polyoxyalkylene dibenzyl phenyl ether sulfate salts, polyoxyalkylene cumyl phenyl ether sulfate salts, polyoxyalkylene dicumyl phenyl ether sulfate salts, polyoxy alkylene naphthyl ether sulfate salts, etc.), polyoxyalkylene alkyl polyhydric alcohol ether sulfate salts, aryl sulfonate salts, α-olefin sulfonate salts, alkylaryl sulfonate salts, alkylaryl disulfonate salts (alkyl diphenyl disulfonate salts, etc.), bis(polyoxyalkylene styryl phenyl ether) succinic acid ester sulfonate salts, alkyl sulfosuccinate salts, alkyl phosphate salts, alkylaryl phosphate salts, polyoxyalkylene alkyl ether ... polyoxyalkylene alkyl aryl ether phosphate salts, polycyclic aryl ether phosphate salts, polyoxyalkylene polycyclic aryl ether phosphate salts, polyoxyalkylene alkyl polyhydric alcohol ether phosphate salts, aromatic sulfonates (alkylnaphthalene sulfonates, naphthalene sulfonates, etc.), aromatic sulfonate formalin condensate salts (alkylnaphthalene sulfonate formalin condensate salts, naphthalene sulfonate formalin condensate salts, creosote oil sulfonate-based formalin condensates, etc.), melamine sulfonate condensates,Examples of the condensate include bisphenol sulfonate salts, alkyl carboxylate salts, polyoxyalkylene alkyl ether carboxylate salts, polycarboxylate salts, turmeric oil, and lignin sulfonate salts.
[0040] When the anionic surfactant is a salt, it may be an alkali metal salt, an alkaline earth metal salt, an ammonium salt, an organic amine salt, or the like. Examples of the alkali metal include sodium, potassium, and lithium. Examples of the alkaline earth metal include magnesium, calcium, and barium. Examples of the organic amine include alkylamines (trimethylamine, triethylamine, monomethylamine, dimethylamine, and the like), alkanolamines (monoethanolamine, diethanolamine, triethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, dimethylethanolamine, and the like), and the like. These anionic surfactants may be used alone or in combination of two or more. As the salt of the anionic surfactant, at least one selected from ammonium salts and organic amine salts is preferred from the viewpoint of adhesion to the matrix resin.
[0041] Examples of cationic surfactants include quaternary ammonium salt type cationic surfactants (lauryl trimethyl ammonium chloride, oleyl methyl ethyl ammonium ethosulfate, etc.), amine salt type cationic surfactants (polyoxyethylene lauryl amine lactate, etc.), and the like.
[0042] Specific examples of amphoteric surfactants include amino acid type amphoteric surfactants (such as sodium laurylaminopropionate), betaine type amphoteric surfactants (such as stearyl dimethyl betaine, lauryl dihydroxyethyl betaine), and the like.
[0043] [Other resins] The fiber sizing agent of the present invention may contain other resins other than the epoxy compound (A). The other resins are not particularly limited as long as they are resins other than the epoxy compound (A), but when they contain at least one selected from the group consisting of other epoxy compounds (C) other than the epoxy compound (A), vinyl ester resins, saturated polyester resins, unsaturated polyester resins, and rosin ester resins, it is preferable from the viewpoint of suppressing fluff that the total ratio of these other resins in the non-volatile content of the sizing agent is 80% by weight or less. The upper limit of the ratio is more preferably 75% by weight, even more preferably 70% by weight, and particularly preferably 65% by weight. On the other hand, the lower limit of the ratio is more preferably 5% by weight, even more preferably 10% by weight, and particularly preferably 15% by weight. Also, for example, 5 to 75% by weight is more preferable, and 10 to 70% by weight is even more preferable.
[0044] The epoxy compound (C) other than the epoxy compound (A) is not particularly limited, and examples thereof include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, alkylphenol novolac type epoxy resins, biphenyl type epoxy resins, dicyclopentadiene type epoxy resins, naphthalene type epoxy resins, and various modified epoxy resins such as amine-modified aromatic epoxy resins.
[0045] The vinyl ester resin is not particularly limited, and examples thereof include epoxy (meth)acrylates obtained by esterifying the epoxy resin with an α,β-unsaturated monocarboxylic acid. Examples of the α,β-unsaturated monocarboxylic acid include acrylic acid, methacrylic acid, crotonic acid, tiglic acid, and cinnamic acid, and two or more of these may be used in combination. Specific examples of the vinyl ester resin include bisphenol-type epoxy resin (meth)acrylate modified products (terminal (meth)acrylate modified resins obtained by reacting the epoxy group of a bisphenol A-type epoxy resin with the carboxyl group of (meth)acrylic acid), and the like.
[0046] The saturated polyester resin is not particularly limited, and examples thereof include aliphatic polyester resins, aromatic polyester resins, etc. Usually, aromatic polyester resins, such as polyalkylene arylate resins or saturated aromatic polyester resins, are used. Examples of aromatic polyester resins include polyC2-4 alkylene terephthalates such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT); polyC2-4 alkylene naphthalates corresponding to these polyalkylene terephthalates (e.g., polyethylene naphthalate); and 1,4-cyclohexyldimethylene terephthalate (PCT). The aromatic polyester resin may be a copolyester containing an alkylene arylate unit as the main component (e.g., 50% by weight or more), and examples of the copolymerization components include C2-6 alkylene glycols such as ethylene glycol, propylene glycol, butanediol, and hexanediol, polyoxy C2-4 alkylene glycols, asymmetric aromatic dicarboxylic acids such as phthalic acid and isophthalic acid or their acid anhydrides, and aliphatic dicarboxylic acids such as adipic acid. Furthermore, a branched chain structure may be introduced into the linear polyester using a small amount of polyol and / or polycarboxylic acid. Furthermore, a modified polyester resin modified with a modifying compound (for example, an aromatic polyester resin having at least one group selected from an amino group and an oxyalkylene group) may be used. Examples of the modifying compound include polyamines (aliphatic diamines such as linear or branched alkylene diamines having about 2 to 10 carbon atoms, such as ethylenediamine, trimethylenediamine, propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, trimethylhexamethylenediamine, 1,7-diaminoheptane, and 1,8-diaminooctane; alicyclic diamines such as isophoronediamine, bis(4-amino-3-methylcyclohexyl)methane, and bis(aminomethyl)cyclohexane; and aromatic diamines such as phenylenediamine, xylylenediamine, and diaminodiphenylmethane; and the like), polyols ((poly)oxy C2-4 alkylene glycols such as (poly)oxyethylene glycol, (poly)oxytrimethylene glycol, (poly)oxypropylene glycol, and (poly)oxytetramethylene glycol). The modification can be carried out, for example, by mixing the polyester resin with a modifying compound under heating, and utilizing an amidation, esterification or transesterification reaction.
[0047] The weight average molecular weight of the saturated polyester resin is preferably from 3000 to 12000, more preferably from 6000 to 11000. The acid value is preferably not more than 5. The weight of the saturated polyester resin in the non-volatile content of the sizing agent is preferably not more than 20%. The weight average molecular weight in the present invention was calculated from the peak measured by a differential refractive index detector using a high-performance gel permeation chromatography apparatus HLC-8320GPC manufactured by Tosoh Corporation, injecting a sample at a concentration of 2 mg / ml into a separation column KF-402HQ or KF-403HQ manufactured by Resonaq (SHODEX).
[0048] The unsaturated polyester resin may be an unsaturated polyester obtained by reacting an acid component containing an α,β-unsaturated dicarboxylic acid with an alcohol. Examples of the α,β-unsaturated dicarboxylic acid include maleic acid, fumaric acid, itaconic acid, and derivatives thereof such as acid anhydrides, and two or more of these may be used in combination. If necessary, saturated dicarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, tetrahydrophthalic acid, adipic acid, and sebacic acid, and derivatives thereof such as acid anhydrides, may be used in combination with the α,β-unsaturated dicarboxylic acid as acid components other than the α,β-unsaturated dicarboxylic acid. Examples of the alcohol include aliphatic glycols such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,2-propanediol, 1,2-butanediol, 1,3-butanediol, and 1,4-butanediol; alicyclic diols such as cyclopentanediol and cyclohexanediol; aromatic diols such as hydrogenated bisphenol A, bisphenol A propylene oxide (1 to 100 mol) adducts, and xylene glycol; and polyhydric alcohols such as trimethylolpropane and pentaerythritol, and two or more of these may be used in combination. Specific examples of unsaturated polyester resins include condensates of fumaric acid or maleic acid with an ethylene oxide (hereinafter abbreviated as EO) adduct of bisphenol A, condensates of fumaric acid or maleic acid with a propylene oxide (hereinafter abbreviated as PO) adduct of bisphenol A, and condensates of fumaric acid or maleic acid with an EO and PO adduct of bisphenol A (the addition of EO and PO may be random or block).
[0049] The weight average molecular weight of the unsaturated polyester resin is preferably 3000 to 12000, more preferably 3000 to 8000. The acid value is preferably not more than 5. The weight of the unsaturated polyester resin in the non-volatile content of the sizing agent is preferably not more than 20%.
[0050] The rosin ester resin is an esterified product derived from rosin, and examples thereof include compounds obtained by esterifying rosin with a hydroxyl group-containing compound.
[0051] Rosin is a natural resin obtained from pine trees, and is a mixture containing abietic acid and its isomers in various proportions. Examples of components other than abietic acid include dehydroabietic acid, dihydroabietic acid, neoabietic acid, pimaric acid, isopimaric acid, levopimaric acid, and palustric acid.
[0052] The hydroxyl group-containing compound is not particularly limited, and examples thereof include compounds having two hydroxyl groups, such as ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, octanediol, dipropylene glycol, and bisphenol A; compounds having three hydroxyl groups, such as glycerin, trimethylolethane, and trimethylolpropane; compounds having four hydroxyl groups, such as pentaerythritol, sorbitan, and diglycerin; and compounds having six hydroxyl groups, such as sorbitol and dipentaerythritol.
[0053] As the rosin ester, a compound obtained by further adding an alkylene oxide such as ethylene oxide or propylene oxide to the above esterified product can also be used. The addition of these alkylene oxides can be carried out according to a conventional method. The weight of the rosin ester resin in the non-volatile content of the sizing agent is preferably 20% or less.
[0054] [Other ingredients] The fiber sizing agent of the present invention may contain at least one component selected from water, an organic solvent, a smoothing agent, an antioxidant, and a preservative as an additional component other than the epoxy compound (A), the surfactant (B), and other resins, within a range that does not impair the effects of the present invention, in order to maintain the performance of the sizing agent and improve its applicability to fibers.
[0055] The fiber sizing agent of the present invention preferably contains 50 to 90% by weight of water in terms of the stability and ease of handling of the treatment agent. The upper limit of the water content in the fiber sizing agent of the present invention is more preferably 85% by weight, and even more preferably 80% by weight. Meanwhile, the lower limit of the water content is more preferably 55% by weight, and even more preferably 60% by weight. Also, for example, 55 to 85% by weight is more preferable, and 60 to 80% by weight is even more preferable.
[0056] From the viewpoints of safety to the human body during handling, prevention of disasters such as fires, prevention of pollution of the natural environment, and the like, the fiber sizing agent of the present invention may contain organic solvents such as alcohol (methyl alcohol, ethyl alcohol, isopropyl alcohol, etc.), glycols (ethylene glycol, diethylene glycol, propylene glycol, butyl glycol, butyl diglycol, isopropyl glycol, etc.), acetone, methyl ethyl ketone, etc., within a range that does not impair the effects of the present invention.
[0057] The fiber sizing agent of the present invention may contain a smoothing agent to suppress fluffing of the strands to which the sizing agent is applied. Examples of the smoothing agent include esters of higher fatty acids and higher alcohols, natural oils and fats (coconut oil, beef tallow, olive oil, rapeseed oil, etc.), liquid paraffin, wax, etc. Examples of higher fatty acids are as described above. Examples of alkyl groups of higher alcohols are as described above as alkyl groups constituting hydrophobic groups. Examples of waxes include polyethylene, polypropylene, polyethylene oxide, polypropylene oxide, modified polyethylene, modified polypropylene, paraffin wax, candelilla wax, carnauba wax, rice wax, beeswax, etc. The amount of the smoothing agent is preferably 0.1 to 10% by weight, and more preferably 0.1 to 5% by weight, based on the non-volatile content of the fiber sizing agent.
[0058] Among the smoothing agents, from the viewpoint of suppressing fuzzing, it is preferable to use fatty acids and / or alcohols having 30 or more carbon atoms, and esters thereof. Examples include candelilla wax and carnauba wax.
[0059] [Textile sizing agent] The fiber sizing agent of the present invention contains the epoxy compound (A) and the surfactant (B), so that it can achieve both adhesion to the matrix resin and inhibition of fuzzing. It is believed that the reason that both adhesion to the matrix resin and suppression of fuzz can be achieved is that the * portion in the epoxy compound (A) is a primary or secondary carbon atom, which increases the linearity of the molecule and reduces friction, thereby suppressing fuzz, and that the surfactant (B) improves the wettability of the epoxy compound (A) to the matrix resin, which in turn improves adhesion to the matrix resin by allowing the epoxy groups in the epoxy compound (A) to react uniformly with the matrix resin, thereby improving adhesion to the matrix resin, thereby enabling both adhesion and suppression of fuzz to be achieved.
[0060] The proportion of the epoxy compound (A) in the non-volatile content of the fiber sizing agent of the present invention is not particularly limited, but is preferably 5% by weight or more from the viewpoint of suppressing fuzz. The lower limit of the proportion is more preferably 10% by weight, further preferably 15% by weight, and particularly preferably 20% by weight. On the other hand, the upper limit of the proportion is more preferably 90% by weight, further preferably 80% by weight, and particularly preferably 70% by weight. Also, for example, 5 to 90% by weight is more preferable, and 10 to 80% by weight is more preferable.
[0061] The proportion of the surfactant (B) in the non-volatile content of the fiber sizing agent of the present invention is not particularly limited, but is preferably 10% by weight or more in terms of the stability of the treatment agent. The lower limit of the proportion is more preferably 15% by weight, and even more preferably 20% by weight. On the other hand, the upper limit of the weight proportion is more preferably 95% by weight, more preferably 60% by weight, and particularly preferably 40% by weight. Also, for example, 10 to 95% by weight is more preferable, and 15 to 60% by weight is even more preferable.
[0062] The weight of the surfactant (B) relative to 100 parts by weight of the epoxy compound (A) in the non-volatile content of the fiber sizing agent of the present invention is not particularly limited, but is preferably 20 to 100 parts by weight in terms of the stability of the treatment agent. The lower limit of the weight ratio is more preferably 25 parts by weight, even more preferably 30 parts by weight, and particularly preferably 35 parts by weight. On the other hand, the upper limit of the weight ratio is more preferably 90 parts by weight, even more preferably 80 parts by weight, and particularly preferably 70 parts by weight. Also, for example, 25 to 90 parts by weight is more preferable, and 30 to 80 parts by weight is even more preferable.
[0063] The fiber sizing agent of the present invention may optionally contain an epoxy compound (C) other than the epoxy compound (A). The weight ratio ((A+C) / B) of the total of the epoxy compound (A) and the other epoxy compound (C) to the surfactant (B) in the non-volatile content of the fiber sizing agent of the present invention is preferably 0.1 to 10 in terms of adhesion to the matrix resin. The upper limit of the weight ratio is more preferably 9, further preferably 8, and particularly preferably 7. On the other hand, the lower limit of the weight ratio is more preferably 0.5, further preferably 1, and particularly preferably 2. Also, for example, 0.5 to 9 is more preferable, and 1 to 8 is even more preferable.
[0064] The complex viscosity of the non-volatile content of the fiber sizing agent of the present invention at 25°C, strain 0.005, and frequency 1 Hz is 1×10 2 ~1×10 5 The upper limit of the complex viscosity is preferably 7×10 4 Pa s is more preferable, 3×10 4 Pa s is more preferable, 9×10 3 On the other hand, the lower limit of the complex viscosity is 3×10 2 Pa s is more preferable, 7×10 2 Pa s is more preferable, and 3×10 3 Pa·s is particularly preferred. For example, 3×10 2 ~7×10 4 Pa s is more preferable, 7×10 2 ~3×10 4 The complex viscosity in the present invention is measured by the method described in the Examples.
[0065] The ester value of the non-volatile content of the fiber sizing agent of the present invention is preferably 1.5 to 500 mgKOH / g in terms of adhesion to the matrix resin. The upper limit of the ester value is more preferably 450 mgKOH / g, even more preferably 200 mgKOH / g, and most preferably 50 mgKOH / g. On the other hand, the lower limit of the ester value is more preferably 2 mgKOH / g, even more preferably 5 mgKOH / g, and particularly preferably 8 mgKOH / g. Also, for example, it is more preferably 2 to 200 mgKOH / g, and even more preferably 5 to 50 mgKOH / g.
[0066] The epoxy equivalent in the non-volatile content of the fiber sizing agent of the present invention is preferably 100 to 10,000 g / eq in terms of adhesion to the matrix resin. The upper limit of the epoxy equivalent is more preferably 5,000 g / eq, even more preferably 3,000 g / eq, and most preferably 1,000 g / eq. On the other hand, the lower limit of the epoxy equivalent is more preferably 150 g / eq, even more preferably 200 g / eq, and particularly preferably 250 g / eq. Also, for example, it is more preferably 150 to 5,000 g / eq, and even more preferably 200 to 3,000 g / eq.
[0067] The method for producing the fiber sizing agent of the present invention is not particularly limited, and known methods can be used. Examples of the method include a method in which each component constituting the sizing agent is added to water under stirring to form an aqueous solution, emulsion, or aqueous dispersion, a method in which each component constituting the sizing agent is made into an aqueous solution, emulsion, or aqueous dispersion when it is produced, a method in which each component constituting the sizing agent is added to water containing a surfactant under stirring to emulsify or disperse, a method in which each component constituting the sizing agent is mixed with an emulsion dispersion liquid that has been previously emulsified and dispersed, a method in which each component constituting the sizing agent is mixed, the mixture obtained is heated to a softening point or higher, and then water is gradually added while applying a mechanical shear force using a homogenizer, homomixer, ball mill, or the like to cause phase inversion emulsification, and a method in which the emulsion dispersion liquid that has been emulsified and dispersed is mixed with water in an oil supply bath to which the sizing agent is applied.
[0068] The fiber sizing agent of the present invention is preferably emulsified and / or dispersed in water from the viewpoint of handling. The average particle size of the sizing agent is not particularly limited, but from the viewpoint of shape retention, it is preferably 10 μm or less, more preferably 0.01 to 1 μm, and even more preferably 0.01 to 0.5 μm. The average particle size in the present invention refers to the arithmetic mean value calculated from the particle size distribution measured by a laser diffraction / scattering type particle size distribution measuring device (LA-920 manufactured by Horiba).
[0069] The non-volatile content of the fiber sizing agent of the present invention is preferably 5 to 55% by weight from the viewpoint of ease of handling. The upper limit of the concentration is more preferably 50% by weight, further preferably 45% by weight, and particularly preferably 40% by weight. On the other hand, the lower limit of the concentration is more preferably 10% by weight, further preferably 20% by weight, and particularly preferably 30% by weight. The non-volatile content concentration can be obtained by spreading 2.0 to 3.0 g of the fiber sizing agent evenly on an aluminum sheet (φ120 to 130 mm), drying it at 110°C under irradiation with an infrared lamp, precisely weighing the weight of the residue on the aluminum sheet when the fluctuation range of the volatile content over 150 seconds becomes 0.15%, and calculating the ratio (percentage) of the remaining weight after heating to the weight before heating.
[0070] The viscosity of the fiber sizing agent of the present invention at 25° C. is preferably 10 to 100,000 mPa·s, and more preferably 10 to 5,000 mPa·s, from the viewpoint of handleability. The viscosity can be measured at a constant temperature of 25° C. using a BL type viscometer.
[0071] From the viewpoint of blend stability, the pH of the fiber sizing agent of the present invention is preferably 2 to 12, more preferably 4 to 10. The pH can be measured at a constant temperature of 25° C. using a pH meter.
[0072] From the viewpoint of cost, etc., it is preferable that the fiber sizing agent of the present invention has a high concentration as described above when distributed and a low concentration (e.g., 0.05 to 5% by weight, etc.) when a fiber bundle is produced. That is, by distributing it at a high concentration, transportation costs and storage costs can be reduced, and by treating the fibers at a low concentration, a fiber bundle that gives an excellent molded body strength can be produced.
[0073] [Fiber strand] The fiber strand of the present invention is a raw fiber strand to which the above-mentioned fiber sizing agent is adhered, and is a fiber for reinforcing a thermosetting resin or a thermoplastic matrix resin.
[0074] The method for producing a fiber strand of the present invention is a production method including a sizing treatment step of applying the above-mentioned fiber sizing agent to a raw fiber strand and drying the resulting applied product. The method for applying the fiber sizing agent to the raw fiber strand to obtain the applied product is not particularly limited, but may be a method for applying the fiber sizing agent to the raw fiber strand by a kiss roller method, a roller immersion method, a spray method, or any other known method. Among these methods, the roller immersion method is preferred because it allows the fiber sizing agent to be applied uniformly to the raw fiber strand. There is no particular limitation on the method for drying the obtained deposit, and for example, it can be dried by heating with a heated roller, hot air, a hot plate, etc. There is no particular limitation on the drying temperature, and it is, for example, 100 to 250°C.
[0075] In addition, when the fiber sizing agent of the present invention is applied to the raw fiber strand, all of the components of the fiber sizing agent may be mixed and then applied, or the components may be applied separately in two or more stages. Furthermore, within the range that does not impair the effects of the present invention, thermosetting resins such as epoxy resins, vinyl ester resins, and phenolic resins and / or thermoplastic resins other than the polymer components of the present invention, such as polyolefin resins, nylon resins, polycarbonate resins, polyester resins, polyacetal resins, ABS resins, phenoxy resins, polymethyl methacrylate resins, polyphenylene sulfide resins, polyetherimide resins, and polyether ketone resins, may be applied to the raw synthetic fiber strand.
[0076] The fiber strand of the present invention is used as a reinforcing fiber for a composite material having various thermosetting resins or various thermoplastic resins as a matrix resin, and may be used in the form of a continuous fiber or cut to a predetermined length.
[0077] The amount of non-volatile matter of the fiber sizing agent adhered to the raw fiber strand can be appropriately selected and may be an amount necessary for the synthetic fiber strand to have the desired function, but the amount is preferably 0.1 to 20% by weight based on the raw fiber strand. In a fiber strand in a continuous fiber state, the amount is more preferably 0.1 to 10% by weight, and even more preferably 0.5 to 5% by weight based on the raw fiber strand. In a strand cut to a predetermined length, the amount is more preferably 0.5 to 20% by weight, and even more preferably 1 to 10% by weight.
[0078] Examples of fibers of the (raw material) fiber strand to which the fiber sizing agent of the present invention can be applied include various inorganic fibers such as carbon fibers, glass fibers, and ceramic fibers, and various organic fibers such as aramid fibers, polyethylene fibers, polyethylene terephthalate fibers, polybutylene terephthalate fibers, polyethylene naphthalate fibers, polyarylate fibers, polyacetal fibers, PBO fibers, polyphenylene sulfide fibers, and polyketone fibers. From the viewpoint of the physical properties of the obtained fiber-reinforced composite material, at least one selected from carbon fibers, aramid fibers, polyethylene fibers, polyethylene terephthalate fibers, polybutylene terephthalate fibers, polyethylene naphthalate fibers, polyarylate fibers, polyacetal fibers, PBO fibers, polyphenylene sulfide fibers, and polyketone fibers is preferred. Carbon fibers are more preferred. The fiber strand of the present invention is a fiber bundle in which at least one type of single yarn (filament) selected from the group consisting of these fibers is bundled together at 3,000 to 100,000. From the viewpoints of handling and shape retention, the number of strands is preferably 10,000 or more, and more preferably 20,000 or more. The synthetic fiber strand of the present invention may be subjected to a fiber-spreading process for widening the strand width. Examples of the fiber-spreading method include rubbing against a metal surface. The temperature during the fiber-spreading process is, for example, 20 to 100°C.
[0079] [Fiber-reinforced composite materials] The fiber reinforced composite material of the present invention contains a thermosetting matrix resin or a thermoplastic matrix resin and the above-mentioned fiber strands. Since the fiber strands have been treated with the fiber sizing agent of the present invention, the affinity between the fiber strands and the thermoplastic matrix resin is improved, resulting in a fiber reinforced composite material with excellent adhesiveness. Here, the matrix resin refers to a matrix resin containing a thermosetting resin or a thermoplastic resin, and may contain one or more types. The thermosetting resin is not particularly limited, and examples thereof include epoxy resin, phenol resin, unsaturated polyester resin, vinyl ester resin, cyanate ester resin, polyimide resin, etc. The thermoplastic resin is not particularly limited, and examples thereof include polyolefin resin, polyamide resin, polycarbonate resin, polyester resin, polyacetal resin, ABS resin, phenoxy resin, polymethyl methacrylate resin, polyphenylene sulfide resin, polyetherimide resin, polyether ketone resin, etc. Among these, thermosetting resin is preferred from the viewpoint of the higher adhesiveness improving effect of the fiber sizing agent of the present invention, and epoxy resin and vinyl ester resin are more preferred.
[0080] These matrix resins may be partially or completely modified for the purpose of further improving the adhesion to the fiber strands. The method for producing the fiber-reinforced composite material is not particularly limited, and known methods such as compound injection molding using chopped fibers or long fiber pellets, press molding using UD sheets or woven sheets, or filament winding molding can be used. The content of the fiber strands in the fiber reinforced composite material is not particularly limited and may be appropriately selected depending on the type and form of the fiber, the type of thermoplastic matrix resin, etc., but is preferably 5 to 70% by weight, more preferably 20 to 60% by weight, of the resulting fiber reinforced composite material. EXAMPLES
[0081] The present invention will be described in detail below with reference to examples, but is not limited to the examples described here. In the following examples, percentages (%) and parts are by weight unless otherwise specified. Each characteristic value was measured according to the method described below.
[0082] <Adhesion rate of sizing agent> Approximately 2 g of the sizing agent-coated carbon fiber bundle was weighed (W1) (read to the fourth decimal place) and then placed in an electric furnace (capacity 120 cm) set to a temperature of 450°C in a nitrogen gas flow of 50 ml / min. 3 ) for 30 minutes to completely decompose the sizing agent. The carbon fiber bundle was then transferred to a container in a 20 L / min dry nitrogen gas flow and cooled for 15 minutes. The carbon fiber bundle was then weighed (W2) (read to four decimal places) and the amount of sizing agent attached was calculated using the following formula. In this example, the measurement was performed twice, and the average value was used as the adhesion rate of the sizing agent. Sizing agent adhesion amount (wt%) = [W1(g)-W2(g)] / [W1(g)]×100
[0083] <Convergence evaluation> The sizing agent-treated carbon fiber strands were cut into short fibers of about 5 mm using stainless steel scissors, and the bundling state (degree of dispersion) was visually judged according to the following criteria. ◯: The short fibers are in almost the same state as before cutting, and have excellent bundling properties. ×: Short fibers are largely scattered or cracked, and bundling ability is poor.
[0084] <Preparation of non-volatile content samples of fiber sizing agents> 2.0 to 3.0 g of the fiber sizing agent was spread evenly on an aluminum sheet (φ120 to 130 mm) and dried at 110°C under irradiation with an infrared lamp. The amount of the residue on the aluminum sheet when the fluctuation range of the volatile content over 150 seconds became 0.15% was regarded as the non-volatile content of the fiber sizing agent.
[0085] <How to make matrix resin drops> Epoxy resin: A drop of a matrix resin prepared by mixing 100 parts by weight of epoxy resin jER828 (manufactured by Mitsubishi Chemical Corporation) and 3 parts by weight of DICY7 (manufactured by Mitsubishi Chemical Corporation) was formed on the carbon fiber filament, and the resin was cured by heating at 80°C for 1 hour and 150°C for 3 hours.
[0086] <Adhesion evaluation> The adhesiveness was evaluated by the microdroplet method using a composite material interface property evaluation device HM410 (manufactured by Toei Sangyo Co., Ltd.). Carbon fiber filaments were taken out from the carbon fiber strands obtained in the Examples and Comparative Examples, and were set in a sample holder. Drops of each matrix resin were formed on the carbon fiber filaments by the above-mentioned method, and samples for measurement were obtained. The measurement sample was set in the device, the drops were clamped by the device blades, and the carbon fiber filaments were run on the device at a speed of 0.06 mm / min, and the maximum pull-out load F when the drops were pulled out from the carbon fiber filaments was measured. The interfacial shear strength τ was calculated by the following formula to evaluate the adhesion between the carbon fiber filament and the matrix resin. The above-mentioned epoxy resin and polyamide resin were used as the matrix resin. Each matrix resin drop was prepared by the method described above. Interfacial shear strength τ (unit: MPa) = F / πdl (F: maximum pull-out load, d: carbon fiber filament diameter, l: particle diameter in the pull-out direction of the drop) The evaluation results were judged according to the following criteria, with ◎ and ◯ being considered pass. ◎:Interfacial shear strength is over 60Mpa ○: Interfacial shear strength is over 50MPa and 60MPa or less ×: Interfacial shear strength is 50 MPa or less
[0087] <Complex viscosity> The non-volatile content of the fiber sizing agent obtained by the above method was used as a measurement sample, and the complex viscosity was measured using a rheometer (HAAKE MARS 40, manufactured by ThermoFisher Scientific) under the following conditions: measurement mode: shear mode, jig used: parallel plate (φ8 mm), plate distance: 0.500 mm, sample temperature: 25°C, frequency: 1 Hz, dynamic strain: 0.005.
[0088] <Fuzz evaluation> Using a TM-type frictional embracing force tester TM-200 (manufactured by Daiei Scientific Instruments Co., Ltd.), the carbon fiber strands obtained in the Examples and Comparative Examples were rubbed 1,000 times (reciprocating speed: 300 times / min) with a tension of 50 g through three mirror-finish chrome-plated stainless steel needles arranged in a zigzag pattern, and the state of fluff on the carbon fiber strands was visually judged according to the following criteria, with ◎ and ◯ being considered as passing. ⊚: No fuzzing was observed, just like before rubbing. ◯: A few fluffs were observed, but were at a level that caused no practical problems. △: A lot of pilling was observed, and some thread breakage was also observed. ×: A great deal of fuzzing and breakage of single yarns was observed.
[0089] The components used in the examples are as follows: [Epoxy compound (A)] (A-1) Adeka Cizer (registered trademark) O-130P (manufactured by ADEKA Corporation, epoxidized soybean oil (epoxy equivalent: 242 g / eq, molecular weight: 975)) (A-2) Adeka Cizer (registered trademark) O-180A (manufactured by ADEKA Corporation, epoxidized linseed oil (epoxy equivalent: 176 g / eq, molecular weight: 983)) (A-3) Adeka Cizer (registered trademark) D-32 (manufactured by ADEKA Corporation, epoxidized fatty acid octyl ester (epoxy equivalent: 370 g / eq, molecular weight: 411)) (A-4) Adeka Cizer (registered trademark) D-55 (manufactured by ADEKA Corporation, epoxidized fatty acid alkyl ester (epoxy equivalent: 330 g / eq, molecular weight: 358)) (A-5) Epoxidized oleic acid shown below
[0090] [Surfactant (B)] (B-1): Emulgen (registered trademark) 420 (manufactured by Kao Corporation, POE oleyl ether) (B-2): Pluronic (registered trademark) L-121 (manufactured by ADEKA Corporation, POEO polyether) (B-3): Pluronic (registered trademark) P-103 (manufactured by ADEKA Corporation, POEO polyether) (B-4): Pluronic (registered trademark) F-108 (manufactured by ADEKA Corporation, POEO polyether) (B-5): Emulgen (registered trademark) A-500 (manufactured by Kao Corporation, POE distyrenated phenyl ether) (B-6): POE hydrogenated castor oil ether (EO 50 mol) In addition, POEO means polyoxypropylene polyoxyethylene.
[0091] [Other epoxy compounds (C)] (C-1): Epotohto (registered trademark) YD-128 (manufactured by Nippon Steel Chemical & Material Co., Ltd.) bisphenol A type epoxy resin (epoxy equivalent: 184 to 194 g / eq) (C-2): Epotohto (registered trademark) YD-011 (Nippon Steel Chemical & Material Co., Ltd.) Bisphenol A type epoxy resin (epoxy equivalent: 440 to 510 g / eq) (C-3): Epotohto (registered trademark) YD-014 (Nippon Steel Chemical & Material Co., Ltd.) Bisphenol A type epoxy resin (epoxy equivalent: 900 to 1000 g / eq) (C-4): jER (registered trademark) 4005P (manufactured by Mitsubishi Chemical Corporation) bisphenol F type epoxy resin (epoxy equivalent: 950 to 1200 g / eq)
[0092] [Other resins (D)] (D-1): Unsaturated polyester shown below (D-2): Saturated polyester shown below
[0093] (E-1): 2-Ethylhexyl stearate (E-2): Oleyl oleate
[0094] [Synthesis of epoxidized oleic acid (A-5)] 145 parts of oleic acid was added to 475 parts of a peracetic anhydride-acetic acid solution with a peracetic acid concentration of 8 weight percent over 15 minutes and reacted at 30°C for 4 hours, after which the reaction liquid was poured into ice water to produce a solid, which was dissolved in petroleum ether, water was added to remove the acid, and the mixture was cooled to -15°C to obtain crystallized epoxidized oleic acid. The epoxy equivalent was 311g / eq.
[0095] [Synthesis of unsaturated polyester (D-1)] The inside of the reactor was replaced with nitrogen gas, and 88 parts of maleic anhydride and 404 parts of an ethylene oxide 4 mole adduct of bisphenol A were charged and reacted at 140°C for 5 hours. Water was distilled off to obtain an unsaturated polyester (D-1) with an acid value of 2.5. The weight average molecular weight Mw was 3,550.
[0096] [Synthesis of saturated polyester resin (D-2)] The inside of the reactor was replaced with nitrogen gas, and 890 parts of dimethyl isophthalate, 118 parts of 5-sodium dimethyl sulfoisophthalate, 530 parts of diethylene glycol, 0.5 parts of zinc acetate, and 0.5 parts of antimony trioxide were charged and reacted at 140 to 220°C for 5 hours. Diethylene glycol was distilled off at 240 to 270°C to obtain a saturated polyester resin (D-2) with an acid value of 3.4. The weight average molecular weight Mw was 10,300.
[0097] [Production of fiber sizing agents and carbon fiber strands with sizing agents] The components other than water shown in Tables 1 to 6 were charged in an emulsifier, and water was gradually added under stirring at 60°C to invert the phase and emulsify, obtaining a sizing agent aqueous dispersion with a non-volatile content of 40% by weight. The obtained sizing agent aqueous dispersion was diluted with water to prepare a sizing agent dilution with a non-volatile content of 3% by weight, and a carbon fiber strand (average diameter 8 μm, number of filaments 24,000) untreated with a sizing agent was immersed and impregnated in the dilution, and then dried with hot air at 120°C for 5 minutes to obtain a sizing agent-adhered carbon fiber strand with a theoretical adhesion of 1.0%. The properties of the sizing agent and the strand were evaluated by the above-mentioned methods. The results are shown in Tables 1 to 4.
[0098] [Table 1]
[0099] [Table 2]
[0100] [Table 3]
[0101] [Table 4]
[0102] As can be seen from Tables 1 to 4, the fiber sizing agents of Examples 1 to 37 were fiber sizing agents containing an epoxy compound (A) and a surfactant (B), and therefore were able to achieve both adhesion to the matrix resin and suppression of fuzz. On the other hand, the fiber sizing agents of Comparative Examples 1 to 8 were fiber sizing agents not containing an epoxy compound (A) and a surfactant (B), and therefore were unable to achieve both adhesion to the matrix resin and suppression of fuzz, and therefore were unable to solve the problem.
Claims
1. A fiber sizing agent comprising an epoxy compound (A) having a structural unit represented by the following general formula (1) and a surfactant (B): 【Chemistry 1】 (In formula 1, * represents the bonding position to a primary carbon atom or a secondary carbon atom.)
2. 2. The fiber sizing agent according to claim 1, wherein the epoxy equivalent in the non-volatile content of the fiber sizing agent is 100 to 10,000 g / eq.
3. 3. The fiber sizing agent according to claim 1, wherein the fiber sizing agent optionally contains another epoxy compound (C) other than the epoxy compound (A), and a weight ratio ((A+C) / B) of the total of the epoxy compound (A) and the other epoxy compound (C) to the surfactant (B) in the non-volatile content of the fiber sizing agent is 0.1 to 10.
4. The complex viscosity of the non-volatile content of the fiber sizing agent at 25° C., strain 0.005, and frequency 1 Hz is 1×10 2 ~1×10 5 The fiber sizing agent according to claim 1 or 2, having a viscosity of Pa·s.
5. 3. The fiber sizing agent according to claim 1, wherein the ester value of the non-volatile matter in the fiber sizing agent is 1.5 to 500 mgKOH / g.
6. A fiber strand having the fiber sizing agent according to claim 1 or 2 deposited thereon.
7. A fiber-reinforced composite material comprising a matrix resin and the fiber strand of claim 6.
8. The fiber-reinforced composite material according to claim 7 , wherein the matrix resin is a thermosetting resin.
Citation Information
Patent Citations
Carbon fiber strand
JP2004169260A
Sizing coated carbon fiber and method for producing the same
JP2005179826A